PRODUCTION OF BIOETHANOL FROM CITRUS FRUIT (CITRUS SP) WASTE BY ACID HYDROLYSIS AND FERMENTATION USING SACCHAROMYCES CEREVISIAE - Andini, Citra; Mahajoeno, Edwi; Setyaningsih, Ratna (Prosiding Seminar Biologi, 2013)
One of the promising biofuel is bioethanol which can be produced from agricultural waste cellulosic biomass such as citrus fruit waste. Bioethanol can be derived from citrus fruit waste that is rarely used. Cellulosecontained in citrus fruit  waste can be converted into ethanol through a process of chemical and biological. Sulfuric acid ( H2SO4) can be used in hydrolysis of cellulose material in citrus fruit waste to producesugars and batch fermentation by Saccharomyces cereviseae can be used to convert sugars into bioethanol.The purpose of this research were to determine the highest reducing sugar from acid hydrolisis with different acid concentration levels of 0, 3, 7, and 10% and to know the highest levels of bioethanol and optimum incubation time. Extracts made from citrus fruit waste without peel. Citrus fruits were hydrolyse using a variation of 1 M H2SO4 acid concentration of 0, 3, 7, and 10 % to produce reducing sugars. Reducing sugars were analyzed using the Nelson Somogyi method.The optimum reducing sugar is used for fermentation by yeast Saccharomyces cerevisiae using a variation of the long incubation days 0, 2, 4, 6, 8 and bioethanol purified by distillation method. Acid hydrolysis resulted reduction sugar 3,5%, at an optimum concentration of 3% is used for fermentation by yeast S. cerevisiae. The highest level of fermentation time of 6 days produced bioethanol having the content 9,75% .  Kata Kunci : Bioethanol, Citrus Acid Waste, Saccharomyces Cerevisiae, Fermentation .